2020
DOI: 10.1002/hyp.13870
|View full text |Cite
|
Sign up to set email alerts
|

Cover crops and precipitation influence soluble reactive phosphorus losses via tile drain discharge in an agricultural watershed

Abstract: Subsurface tile drainage speeds water removal from agricultural fields that are historically prone to flooding. While managed drainage systems improve crop yields, they can also contribute tothe eutrophication of downstream ecosystems, as tile-drained systems are conduits for nutrients to adjacent waterways. The changing climate of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…(2015) also observed higher P sorption and lower bioavailable P in one site with higher concentrations of iron oxides than in a nearby site that had lower iron oxides. Furthermore, a companion study found that cover crops were also more effective in reducing P loss from soils to tile drains in SDW than in KDW and attributed these results to the underlying geochemical properties and legacy fertilizer application described above (Trentman et al., 2020).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…(2015) also observed higher P sorption and lower bioavailable P in one site with higher concentrations of iron oxides than in a nearby site that had lower iron oxides. Furthermore, a companion study found that cover crops were also more effective in reducing P loss from soils to tile drains in SDW than in KDW and attributed these results to the underlying geochemical properties and legacy fertilizer application described above (Trentman et al., 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Differences in geochemical properties between the watersheds could also play a role in the extent to which cover crops affect soil P. Clay soils in KDW are likely more conducive to inorganic P retention because both extractable iron and aluminum are more abundant relative to P (Trentman et al., 2020). This higher abundance of iron and aluminum relative to P allows for more P sorption capacity (Andersson et al., 2015) and reduced potential for cover crop uptake in KDW vs. SDW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the eld scale, we expected to see lower DSi concentrations in water from tiles draining elds planted with cover crops versus those without cover crops, particularly during the fall and early winter when cover crops were actively growing. Because cover crops at this study location strongly reduce N loss (Hanrahan et al 2018, Trentman et al 2020 In Review), we predicted water from tile drains in cover cropped elds would have a higher Si:N molar ratio than elds without cover crops. The effect of cover crops on P loss to surface water is variable, and depends, in part, on precipitation patterns (Trentman et al 2020), thus we expected no strong directionality in the response of Si:P molar ratios to winter cover crops.…”
Section: Introductionmentioning
confidence: 99%
“…In agricultural watersheds, farmers often implement conservation practices to reduce nutrient losses from their fields to adjacent waterways, and include conservation tillage practices (Allmaras & Dowdy, 1985; Phillips et al, 1980), the two‐stage ditch (Mahl et al, 2015; Roley et al, 2012; Speir et al, 2020), and the planting of winter cover crops in the fallow season (Hanrahan et al, 2018; Kaspar & Singer, 2011; Kladivko et al, 2014; Strock et al, 2004; Trentman et al, 2020). Given the pervasive water quality challenges in agricultural landscapes, effective conservation practices are needed, but the patchwork geomorphology of rivers means an alteration within the watershed at the field scale may be masked when exploring dynamics at the watershed scale (De Jager & Houser, 2012; De Paula, Gerhard, De Barros Ferraz, & Wenger, 2018).…”
Section: Introductionmentioning
confidence: 99%